2016
DOI: 10.1590/s1679-45082016md3658
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative near-infrared fluorescent imaging during robotic operations

Abstract: The intraoperative identification of certain anatomical structures because they are small or visually occult may be challenging. The development of minimally invasive surgery brought additional difficulties to identify these structures due to the lack of complete tactile sensitivity. A number of different forms of intraoperative mapping have been tried. Recently, the near-infrared fluorescence imaging technology with indocyanine green has been added to robotic platforms. In addition, this technology has been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A promising technique to visualize healthy and diseased parathyroid tissue has emerged in the use of intraoperative NIRF imaging using intravenously administered indocyanine green (ICG). This safe and rapidly evolving intraoperative imaging modality is described for use in a wide range of surgical procedures, such as identification of the biliary anatomy, assessment of anastomotic perfusion, and sentinel lymph node mapping . Suh et al showed fluorescent PGs when using NIRF imaging with ICG in three dogs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising technique to visualize healthy and diseased parathyroid tissue has emerged in the use of intraoperative NIRF imaging using intravenously administered indocyanine green (ICG). This safe and rapidly evolving intraoperative imaging modality is described for use in a wide range of surgical procedures, such as identification of the biliary anatomy, assessment of anastomotic perfusion, and sentinel lymph node mapping . Suh et al showed fluorescent PGs when using NIRF imaging with ICG in three dogs .…”
Section: Introductionmentioning
confidence: 99%
“…This safe and rapidly evolving intraoperative imaging modality is described for use in a wide range of surgical procedures, such as identification of the biliary anatomy, assessment of anastomotic perfusion, and sentinel lymph node mapping. [14][15][16] Suh et al showed fluorescent PGs when using NIRF imaging with ICG in three dogs. 17 Other studies showed the possibility of ICG fluorescent angiography to assess the remaining blood supply to the PGs in humans.…”
Section: Introductionmentioning
confidence: 99%
“…As proper lymphadenectomy is crucial for an adequate oncological operation for gastric cancer, near infrared imaging improves visualization of vascular anatomy and lymph node identification 47. This technology has been incorporated into multiple specialties as well preventing organ injuries such as to the ureter and biliary ducts 48. In the field of colorectal surgery, in addition to its use in primary surgery, near infrared imaging has been used as a guide for resection of liver metastasis as well as detection of peritoneal carcinomatosis 49.…”
Section: New Technologies In Robotic Surgery Systemmentioning
confidence: 99%